Environanotechnology - Fan, Maohong (Elsevier, 2010)
Understanding and utilizing the interactions between environment and nanoscale materials is a new way to resolve the increasingly challenging environmental issues we are facing and will continue to face. Environanotechnology is the nanoscale technology developed for monitoring the quality of the environment, treating water and wastewater, as well as controlling air pollutants. Therefore, the applications of nanotechnology in environmental engineering have been of great interest to many fields and consequently a fair amount of research on the use of nanoscale materials for dealing with environmental issues has been conducted. The aim of this book is to report on the results recently achieved in different countries. It provides useful technological information for environmental scientists and will assist them in creating cost-effective nanotechnologies to solve critical environmental problems, including those associated with energy production.-Presents research results from a number of countries with various nanotechnologies in multidisciplinary environmental engineering fields -Gives a solid introduction€to the basic theories needed for understanding how environanotechnologies can be developed cost-effectively, and when they should be applied in a responsible manner -Includes worked examples that put environmental problems in€context to show the actual connections between nanotechnology and environmental engineering.
Keywords: Nanotechnology -- Environmental aspects.; Nanostructured materials -- Environmental aspects.; elektronické knihy; electronic books